REM sleep behavior disorder and other sleep abnormalities in p. A53T SNCA mutation carriers. Issue 5 (24th November 2020) - Simitsi, Athina Maria; Koros, Christos; Stamelou, Maria; Papadimitriou, Dimitra; Leonardos, Athanasios; Bougea, Anastasia; Papagiannakis, Nikolaos; Pachi, Ioanna; Angelopoulou, Efthalia; Lourentzos, Konstantinos; Bonakis, Anastasios; Stefanis, Leonidas
Abstract: Study Objectives: Τo assess whether REM Sleep Behavior Disorder (RBD) and other sleep abnormalities occur in carriers of the p.A53T alpha-synuclein gene ( SNCA ) mutation, using both subjective and objective measures. Methods: We have assessed 15 p.A53T carriers (10 manifesting Parkinson's Disease [PD-A53T] and 5 asymptomatic carriers) with simultaneous Video-PSG (polysomnography) recording, the Epworth Sleepiness Scale (ESS) for daytime sleepiness, the Athens Insomnia Scale (AIS), the RBD Screening Questionnaire (RBDSQ) for clinical features of RBD, the Montreal Cognitive Assessment (MOCA) for cognition and the University of Pennsylvania Smell Identification Test (UPSIT) for olfaction. Results: In our cohort, 90% of PD carriers had at least one sleep disorder and 40% had two: 4 RBD, 1 Periodic Limb Movements (PLM), 1 RBD plus PLM, 2 RBD plus moderate Obstructive Sleep Apnea (OSA), and 1 moderate OSA plus Restless Leg Syndrome. No asymptomatic carrier manifested a confirmed sleep disorder. 6/7 PD carriers with RBD had abnormal olfactory testing and 4/7 MOCA below cut off. There was a correlation of both impaired olfaction and cognition with RBD. Conclusions: RBD occurs in the majority of PD-A53T, in contrast to most other genetic forms of PD, in which RBD is uncommon. The paucity of a sleep disorder in the asymptomatic carriers suggests that such carriers have not yet reached the prodromal phase when such sleep disorders manifest. Hyposmia in almost all subjects with RBD and cognitive decline in most of them are indicative of the general pattern of disease progression, which however is not uniform.